MEASURING THE SHIFTING FACTORS THAT CONTRIBUTE TO CONSUMERS’ USE OF GREEN SKINCARE CLEANSERS - Azzahra, Syifa; Iskandar, Budi Permadi (Journal of Business and Management, 2021)
The increasing demand and supply of conventional skincare products have caused severe damage towards the environment. The environmental damage caused by conventional skincare products have driven both producers and consumers to shift their interest towards a more sustainable and eco-friendly option which is green skincare. It is important that consumers start shifting from conventional skincare to green skincare. However, the problem consumers are still reluctant to entirely shift from conventional skincare to green skincare due to their misconception that green skincare cannot outperform conventional skincare in terms of its functionality and benefits to the skin. In order to convince consumers that green skincare can perform as well as or even better than conventional skincare, this study will conduct an analysis regarding the comparison of both products. The objective of this research is to analyse the relevance of product price, product reviews, and product benefits in shifting consumers’ behavior to use green skincare cleansers over conventional skincare cleansers. The Multiple Linear Regression (MLR) will be used to process the quantitative survey data of 200 samples. Keywords: Green Skincare, Conventional Skincare, Cleanser, Shifting Factors, Consumer Usage,Multiple Linear Regression